POSTUR KERJA, KEBIASAAN MEROKOK DENGAN KELUHAN MUSCULOSKELETAL DISORDERS (MSDs) PADA PEKERJA PRODUKSI DI AREA TFD (TALL FORM DRIER) 500 PT SARIHUSADA GENERASI MAHARDHIKA YOGYAKARTA (UNIT I) - Salma Annisa, Nur Mayra; Arianto, Machfudz Eko (Universitas Lambung Mangkurat, 2020)
Work posture is a series of activities carried out by workers in carrying out their work, so work posture can be used as a determining point for the effectiveness of a job. Production workers carry out their work with bending, lifting and repetitive movements for long periods of time. So that workers experience complaints of pain in the skeletal muscles or commonly referred to as symptoms of Musculoskeletal Disorder. Complaints of Musculoskeletal Disorder (MSDs) felt by workers can be caused by several factors such as odd work postures and smoking habits in production workers. This study aims to determine the relationship between work posture, smoking habits in production workers. This study aims to determine the relationship between work posture, smoking habits and complaints of Musculoskeletal Disorder (MSDs) in production workers in the 500 TFD (Tall Form Drier) area of PT Sarihusada Generasi Mahardhika Yogyakarta (Unit I). This type of research is a quantitative study with a cross sectional study design. The sample used in this study were 40 respondents to production workers, with the sampling technique using totality sampling. The instrument used to measure complaints of Musculoskeletal Disorder (MSDs) and smoking habits in workers is to use the Nordic Body Map sheet, while to analyze work posture is the Workplace Ergonomic Risk Assessment (WERA) observation sheet. Data analysis using fisher exact test. The results of the study based on bivariate analysis showed that there was a relationship between work posture (p value of 0.026 Ë‚ 0.05) and smoking habits (p value of 0.002 Ë‚ 0.05) with complaints of Musculoskeletal Disorder (MSDs). Conclusion There is a statistical relationship between work posture and smoking habits with complaints of Musculoskeletal Disorder (MSDs) among production workers in the 500TFD (Tall Form Drier) area of PT Sarihusada Generasi Mahardhika Yogyakarta (Unit I).